Molecular-Based Detection of Leishmania infantum in Human Blood Samples in a New Focus of Visceral Leishmaniasis in Lorestan Province, Iran - Leila Masoori; Farnaz Kheirandish; Ali Haghighi; Mehdi Mohebali; Behnaz Akhoundi; Niloofar Taghipour; Latif Gachkar; Ali Chegeni-Sharafi; Vahideh Moin-Vaziri (Tehran University of Medical Sciences, 2018)
Background: The fatal form of leishmaniasis is visceral form (VL), found in some of the countries in the world. Visceral leishmaniasis has been reported sporadically from all provinces in Iran, including Lorestan. This study aimed to characterize parasite species in DAT positive and some of the DAT negative human blood samples of Delfan district, Lorestan Province, central Iran. Methods: Blood samples were collected from different geographical areas of Delfan. Serum was used for DAT test and remained part of molecular study. DNA was extracted by using DNG-plus extracted kit (Cinagen, Iran). Polymerase chain reaction amplification of Leishmania kDNA and PCR-RFLP of ITS1 was done to identify Leishmania species. Some amplicons were sequenced, submitted to GenBank and analyzed by BLASTn. Results: Expected band of kDNA for L. infantum (720bp) was amplified in 16 out of 186 (8.6%) samples which showed previously anti-Leishmania antibody at different titers or were negative serologically. Using BLASTn, 93% similarity with L. infantum has been shown. The rDNA-ITS1 was amplified only in 9 samples (4.7%). RFLP pattern was similar to what expected for L. infantum. Conclusion: A new emerging hypo-endemic focus, caused by L. infantum, is going to be established in Delphan District, Lorestan Province. Further studies on vector and reservoirs are necessary for the region and other parts of Lorestan Province.